Peran Profitabiltas dalam Memediasi Faktor–Faktor yang Mempengaruhi Nilai Perusahaan pada Perusahaan Manufaktur di BEI - Anita Tarihoran; Suriani Ginting; Robinhot Gultom (Jurnal Ilmiah METHONOMI, 2025)
This study aims to examine and analyze the influence of liquidity, leverage, company size, managerial ownership, and growth opportunity on company value by looking at profitability's ability to mediate. The type of research used is descriptive quantitative. The sampling technique used is purposive sampling with a population of 221 companies and a sample of 91 companies. The data for this study were obtained from the financial reports of manufacturing companies listed on the Indonesia Stock Exchange for the period 2020-2023. The type of research used in this study is quantitative research with the Partial Least Statistics - Structural Equation Modeling method. The analysis results indicate that profitability can mediate the influence of liquidity on company value. However, leverage, managerial ownership, and growth opportunities cannot be mediated through profitability on company value in manufacturing companies listed on the Indonesia Stock Exchange for the period 2020-2023.